2016
DOI: 10.3389/fpls.2016.00011
|View full text |Cite
|
Sign up to set email alerts
|

Microarray Analysis of Rice d1 (RGA1) Mutant Reveals the Potential Role of G-Protein Alpha Subunit in Regulating Multiple Abiotic Stresses Such as Drought, Salinity, Heat, and Cold

Abstract: The genome-wide role of heterotrimeric G-proteins in abiotic stress response in rice has not been examined from a functional genomics perspective, despite the availability of mutants and evidences involving individual genes/processes/stresses. Our rice whole transcriptome microarray analysis (GSE 20925 at NCBI GEO) using the G-alpha subunit (RGA1) null mutant (Daikoku 1 or d1) and its corresponding wild type (Oryza sativa Japonica Nipponbare) identified 2270 unique differentially expressed genes (DEGs). Out of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(63 citation statements)
references
References 49 publications
1
62
0
Order By: Relevance
“…The null mutant of the RGA1 gene exhibits a severe dwarf phenotype in rice [33,34], whereas the down-regulation of the expression of the RGA1 gene causes a semi-dwarf phenotype [19]. Microarray analysis of RGA1 showed that RGA1 might participate in the regulation of multiple abiotic stresses, such as drought, salinity, heat, and cold tolerance [35]. During drought, rga1 mutant plants exhibit greater stomatal conductance than the WT, but both genotypes exhibit the same transpirational water loss per unit leaf area [25].…”
Section: Discussionmentioning
confidence: 99%
“…The null mutant of the RGA1 gene exhibits a severe dwarf phenotype in rice [33,34], whereas the down-regulation of the expression of the RGA1 gene causes a semi-dwarf phenotype [19]. Microarray analysis of RGA1 showed that RGA1 might participate in the regulation of multiple abiotic stresses, such as drought, salinity, heat, and cold tolerance [35]. During drought, rga1 mutant plants exhibit greater stomatal conductance than the WT, but both genotypes exhibit the same transpirational water loss per unit leaf area [25].…”
Section: Discussionmentioning
confidence: 99%
“…The G-protein α subunits also play important roles in the signal transduction pathway of abiotic stress in plants [26]. The full transcriptome microarray analysis of rice revealed that rice RGA1 can regulate low temperature, salt, and drought stress and transmit stress signals to the small phosphorylase GTPase and corresponding effector proteins or molecules, such as ion channels [28]. In the pea, expression of the PsGPA1 gene was significantly changed by NaCl and high temperature [29].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that GPA1 in Arabidopsis is involved in oxidative stress signal transduction and can positively regulate the abiotic stress factors upstream of reactive oxygen species (ROS) and nicotinamide adenine dinucleotide phosphate (NADPH) [27]. Arabidopsis Gα subunit mutations reduced the sensitivity of the plant to ozone stress [28]. In the pea (Pisum sativum Linn.…”
Section: Introductionmentioning
confidence: 99%
“…DSM1 was required for the normal expression of two ROS-scavenging genes, OsPOX22.3 and OsPOX8.1 (Ning et al, 2010). LEA3-1 was considered as a protectant for desiccation and oxidation stress (Jangam et al, 2016). To see whether idr1-1 mutant has increased expression levels of the ROS-scavenging genes due to mutation of IDR1, we further checked the transcript levels of a dozen or so genes implicated in ROS scavenging.…”
Section: Idr1-1 Mutation Impairs Apoplastic and Chloroplatic Ros Prodmentioning
confidence: 99%
“…Data from other studies revealed that RGA1 regulated expression of an abundant group of genes. For example, in rga1 mutant, there were 626 genes, which separately responded to heat (522), drought (101), salt (37), and cold (15) stresses, found to be changed in gene expression levels (Jangam et al, 2016).…”
Section: Idr1-1 Mutation Increases Gene Expression Of Drought-toleranmentioning
confidence: 99%